2017
DOI: 10.1074/jbc.m117.808063
|View full text |Cite
|
Sign up to set email alerts
|

β1 integrin–dependent Rac/group I PAK signaling mediates YAP activation of Yes-associated protein 1 (YAP1) via NF2/merlin

Abstract: Cell adhesion to the extracellular matrix or to surrounding cells plays a key role in cell proliferation and differentiation and is critical for proper tissue homeostasis. An important pathway in adhesion-dependent cell proliferation is the Hippo signaling cascade, which is coregulated by the transcription factors Yes-associated protein 1 (YAP1) and transcriptional coactivator with PDZ-binding motif (TAZ). However, how cells integrate extracellular information at the molecular level to regulate YAP1's nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 53 publications
7
102
1
Order By: Relevance
“…RAC/PAK1 is a major regulator of YAP1, a crucial molecule in Hippo signaling that plays key roles in cell proliferation, differentiation, and apoptosis . Silencing of PSMC2 in osteosarcoma cell lines significantly suppressed cell proliferation, enhanced apoptosis, and accelerated G2/M phase and/or S‐phase arrest .…”
Section: Discussionmentioning
confidence: 99%
“…RAC/PAK1 is a major regulator of YAP1, a crucial molecule in Hippo signaling that plays key roles in cell proliferation, differentiation, and apoptosis . Silencing of PSMC2 in osteosarcoma cell lines significantly suppressed cell proliferation, enhanced apoptosis, and accelerated G2/M phase and/or S‐phase arrest .…”
Section: Discussionmentioning
confidence: 99%
“…Integrins play a crucial role in mediating the signaling from ECM, and multiple connections are identified between integrins and YAP activity. Integrin‐linked kinase can inhibit the Merlin activation by inhibiting phosphatase MYPT1 or through activating RAC and PAK (Sabra et al, 2017; Serrano, McDonald, Lock, Muller, & Dedhar, 2013). Furthermore, it is found (Chakraborty et al, 2017) that the integrin‐mediated regulation of Hippo signaling is linked to focal adhesion kinase (FAK).…”
Section: The Molecular Cascade Involved In the Control Of Eb Formatiomentioning
confidence: 99%
“…Moreover, the past memory of ESC/iPSCs and methods of EB formation, as well as external and internal signals could affect the differentiation and the fate of EBs (Boraas, Guidry, Pineda, & Ahsan, 2016; Vining & Mooney, 2017). Recently, alternative methods of EB formation have been developed that allow for highly accurate control of EBs size, shape, and external biochemical and biomechanical signals, resulting in reproducibly produced homogeneous EBs with the simulation of cell signaling pathways (Sabra et al, 2017; Sato, Idiris, Miwa, & Kumagai, 2016; Son et al, 2017). Now, a fundamental question arises regarding whether the size of EBs, uniformity, and topological microstructure are determined by accidentally spherical agglomerated cells or the cell aggregate under a programmed process and elaborate molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, how the mechanical cues embedded within the extracellular matrix are translated into a functional regulation of YAP and TAZ nuclear shuttling remains elusive. We and others have identified that integrin-dependent cell adhesion and in particular β1 integrins are of critical importance for YAP/TAZ nuclear shuttling [13,14]. Indeed, β1 integrin dependent cell adhesion-signaling, likely through the Src family kinases, leads to the recruitment and activation of Rac-1 at protrusive cell borders, and stimulates a PAK1 dependent signaling cascade resulting in merlin phosphorylation.…”
Section: Introductionmentioning
confidence: 97%